Long-Term Clinical Study on Sandblasted–Acid-Etched Surface Dental Implants: 12-Year Follow-Up - Velasco-Ortega, Eugenio; Pato-Mourelo, Jesús; López-López, Borja; Monsalve-Guil, Loreto; Moreno-Muñoz, Jesús; López-López, José; Núñez-Márquez, Enrique; Matos Garrido, Nuno; Rondón-Romero, José Luis; Jiménez-Guerra, Álvaro; Ortiz-García, Iván (Materials, 2025)
Sandblasting and acid etching are common procedures used to treat implant surfaces, enhancing osseointegration and improving clinical success rates. This clinical study aimed to evaluate the long-term outcomes of sandblasted and acid-etched implants. A total of 303 implants were placed in 114 partially and totally edentulous patients using a two-stage surgical technique and an early loading protocol (6–8 weeks). Clinical findings for implants and prosthetics were evaluated over a 12-year follow-up period. A total of 12 implants (3.9%) failed, with 3 failures occurring during the healing period before loading and 9 due to peri-implantitis. The cumulative survival rate for all implants was 96.1%. A total of 156 prostheses were placed on 300 implants, 87 single crowns, 45 partial fixed bridges, 9 full-arch fixed restorations, and 15 overdentures. The mean marginal bone loss was 1.18 mm. (SD. 0.64 mm.). Thirty-nine implants (13%) in twenty-four patients exhibited peri-implantitis. Technical complications, including prosthetic screw loosening or fracture, ceramic chipping, and acrylic fractures, were observed in 24 subjects (21.1%). Sandblasted and acid-etched surface implants placed in the maxilla and mandible reported favorable outcomes and stable tissue conditions with an early loading protocol.